Nutrition and golf performance: a systematic scoping review - O`Donnell, A.; Murray, A.; Nguyen, A.; Salmon, T.; Taylor, S.; Morton, J. P.; Close, G. L. (Sports Medicine, 2024)
Background: Golf is played both recreationally and professionally by approximately 66.6 million people worldwide. Despite the potential for nutrition to influence golf performance, research in this area is somewhat limited. Objective: To identify the existing literature regarding nutrition and golf and where the current research gaps lie. Design: Scoping review. Online databases were used to retrieve data from 2003 to the present day. Data Sources: A three-step search strategy identified relevant primary and secondary articles as well as grey literature. Published and unpublished articles in the English language, identified by searching electronic databases (ProQuest Central, Web of Science, Scopus, SPORTDiscus and PubMed) and reference searching. Review Methods: Relevant identified studies were screened for final inclusion. Data were extracted using a standardised tool to create a descriptive analysis and a thematic summary. In summary, studies were included if they focused on nutrition, hydration, energy requirements, supplements, or body composition in relation to golf. Results and Discussion: Our initial search found 3616 relevant articles. Eighty-two of these articles were included for the scoping review. Nutrition has the potential to impact golf performance in areas including the maintenance of energy levels, cognitive function, and body composition. Currently, there is limited research available discussing the effects of nutrition interventions related specifically to golf performance. Conclusion: This scoping review highlights that more work is needed to provide golfers and practitioners with golf-specific nutrition research. The key areas for future golf-specific nutrition research include nutrition on cognitive performance, body composition, energy requirements, supplementation, and the potential role of nutrition for the travelling golfer. Systematic reviews could also be used to identify future priorities for nutrition and golf research.